Address at the Annual Meeting of the Life Insurance Association of America - Meyer, Eugene (World Bank, Washington, DC, 2019)
Eugene Meyer, the recently resigned President of the International Bank for Reconstruction and Development, spoke about stepping down to allow a permanent head to take over operations. He spoke about insurance companies of the nation and how they are an important factor in its social security. He discussed the Bank's lending operations. Most of the funds must be obtained through the sale of debentures in the public markets from time to time. The security behind the Bank's obligations its reserves, its paid-in capital on hand and its ability to call upon its members for part or all of the remaining eighty percent of their subscriptions. He highlighted the importance of the International Monetary Fund which has the task of bringing stability into the chaotic area of international currency exchange. He concluded by saying that whether we live in a borrowing or lending country we can all play our part in improving international relations and in strengthening the forces which benefit men in their daily lives.